Race woman : the lives of Shirley Graham Du Bois - Horne, Gerald (New York : New York University Press, 2000)
"A woman of many talents, Graham Du Bois was a controversial figure who at various times championed the civil rights movement in America, the liberation struggles in Africa and the socialist development of Maoist China. Politically and culturally active long before she married W.E.B. Du Bois, Graham Du Bois wore many hats and lived many lives. Horne tells her remarkable story, exploring her work as a Harlem Renaissance playwright, biographer, composer, teacher, novelist, Left political activist, advisor and inspiration."--Jacket
Introduction: Perspectives 16 -- 1 Family 38 -- 2 On Her Journey Now 52 -- 3 The Middle of Her Journey 71 -- 4 Crossroads 89 -- 5 Shirley Graham Du Bois 115 -- 6 Home 134 -- 7 On the Road Again 152 -- 8 Mother, Africa 173 -- 9 Detour 197 -- 10 Black, to the Left 217 -- 11 The End of Her Journey 243.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Du Bois, Shirley Graham, -- 1896-1977.; Du Bois, W. E. B. -- 1868-1963.; Du Bois, Shirley Graham, -- 1896-1977; Du Bois, W. E. B. -- 1868-1963; Du Bois, Shirley Graham; African American women -- Biography; African Americans -- Biography; African American women political activists -- Biography; African Americans -- Politics and government -- 20th century; African Americans -- Intellectual life -- 20th century; African American authors -- Biography; Noires américaines -- Biographies; Noirs américains -- Biographies; Femmes activistes noires américaines -- Biographies; Noirs américains -- Politique et gouvernement -- 20e siècle.; Noirs américains -- Vie intellectuelle -- 20e siècle.; Écrivains noirs américains -- Biographies; SOCIAL SCIENCE -- Women's Studies; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; African American authors; African American women; African American women political activists; African Americans; African Americans -- Intellectual life; African Americans -- Politics and government; 1900-1999; The; available; biography; dynamic; first; influential; paperback; woman151now.; Biography; Biographies; Biographies; Biographies